Marked Directional Skull Asymmetry in the Araucan Horse - Parés-Casanova, Pere M.; Crosby-Granados, René Alejandro; Muñoz, Fabián; Salamanca-Carreño, Arcesio (VCOT Open, 2020)
Background Deviations from the perfect symmetry of normally bilateral symmetrical characters occur during individual development due to the influence of multiple factors. Fluctuating asymmetry (FA) is the random developmental variation of a trait (or character) that is perfectly symmetrical, on average, across a population. Directional asymmetry (DA) occurs when one side of the pair of body sides is strongly more marked.Objective We investigated the presence and level of skull FA and DA in the Araucan horse, a breed from East Colombia.Study Design A sample of 21 skulls belonging to adult animals was studied by means of standard geometric–morphometric methods using 16 landmarks on the dorsal aspect of the crania.Results Measurements showed a significant DA with a consistent rightward shift of the splanchnocrania.Conclusions The results of this study raise questions about the influence of masticatory biomechanics on the asymmetric development of the skull, and also about how management and ingesta-specific properties (such as abrasiveness) may influence this asymmetry.
Keywords: Araucan; bilateral asymmetry; directional asymmetry; fluctuating asymmetry